Characterization of the median sacral artery course at the sacral promontory using contrast-enhanced computed tomography. (January 2017) - Zilberlicht, Ariel; Molnar, Ron; Pal-Ohana, Hanni; Haya, Nir; Auslender, Ron; Abramov, Yoram
Abstract Introduction and hypothesis Laparoscopic sacral colpopexy (SC) is increasingly utilized in the surgical management of apical prolapse. It involves attachment of a synthetic mesh to the sacral promontory and to the prolapsed vaginal walls. The median sacral artery (MSA) runs close to the site of mesh attachment and is therefore prone to intraoperative injury, which may lead to profound hemorrhaging. The aim of this study was to determine the location of the MSA at the level of the sacral promontory with regard to adjacent visible anatomical landmarks. Surgeons may use this information to reduce the risk for presacral bleeding. Methods Sixty consecutive contrast-enhanced pelvic computed tomography scans were revised, and the location of the MSA at the level of the sacral promontory was determined in relation to the ureters, iliac arteries, sacral midline, and aortic bifurcation. Results The MSA runs 0.2 ± 3.9 mm left to the midline of the sacral promontory and 48.0 ± 15.4 mm caudal to the aortic bifurcation. The ureters, internal and external iliac arteries on the right were significantly closer to the MSA than on the left (30.0 ± 7.1 vs 35.2 ± 8.8 mm, p  = 0.001; 21.5 ± 6.8 vs 30.3 ± 8.4 mm, p  < 0.0001; 32.8 ± 10.2 vs 41.9 ± 14.5 mm, p  = 0.005 respectively). Conclusions The MSA, which runs left to the midline of the sacral promontory, and its location can be determined intraoperatively in relation to adjacent visible anatomical structures. The iliac vessels and ureter on the right are significantly closer to the MSA than those on the left. This information may help surgeons performing SC to avoid MSA injury, thus reducing operative morbidity.